Comparison of etomidate and sodium thiopental for induction during rapid sequence intubation in convulsive status epilepticus: A retrospective single-center study. (October 2018) - Perier, François; Chateauneuf, Anne-Laure; Jacq, Gwenaëlle; Holleville, Mathilde; Schnell, David; Merceron, Sybille; Cavelot, Sébastien; Richard, Olivier; Legriel, Stéphane; ,
Highlights: Etomidate and sodium thiopental can be used for rapid sequence intubation in convulsive status epilepticus. Seizure and/or status epilepticus recurrence occurred in similar proportion with both agents. Both agents were associated with hemodynamic instability after rapid sequence intubation. Difficult intubation occurred in similar proportion with both agents. Abstract: Purpose: Few outcome data are available about morbidity associated with endotracheal intubation modalities in critically ill patients with convulsive status epilepticus. We compared etomidate versus sodium thiopental for emergency rapid sequence intubation in patients with out-of-hospital convulsive status epilepticus. Methods: Patients admitted to our intensive care unit in 2006–2015 were studied retrospectively. The main outcome measure was seizure and/or status epilepticus recurrence within 12 h after rapid sequence intubation. Results: We included 97 patients (60% male; median age, 59 years [IQR, 48–70]). Median time from seizure onset to first antiepileptic drug was 60 min [IQR, 35–90]. Reasons for intubation were coma in 95 (98%), acute respiratory distress in 18 (19%), refractory convulsive status epilepticus in 9 (9%), and shock in 6 (6%) patients; 50 (52%) patients had more than one reason. The hypnotic drugs used were etomidate in 54 (56%) and sodium thiopental in 43 (44%) patients. Seizure and/or status epilepticus recurred in 13 (56%) patients in the etomidate group and 11 patients (44%) in the sodium thiopental group (adjusted common odds ratio [aOR], 0.98; 95%CI, 0.36–2.63; P = 0.97). The two groups were not significantly different for proportions of patients with hemodynamic instability after intubation (aOR, 0.60; 95%CI, 0.23–1.58; P = 0.30) or with difficult endotracheal intubation (OR, 1.28; 95% CI 0.23 to 7.21; P=0.77). Conclusions: Our findings argue against a difference in seizure and/or status epilepticus recurrences rates between critically ill patients with convulsive status epilepticus given etomidate vs. sodium thiopental as the induction agent for emergency intubation.